Biomedical Applications: Single Continuous Wave Laser Induced Photodynamic/Plasmonic Photothermal Therapy Using Photosensitizer‐Functionalized Gold Nanostars (Adv. Mater. 22/2013). (10th June 2013) - Wang, Shouju; Huang, Peng; Nie, Liming; Xing, Ruijun; Liu, Dingbin; Wang, Zhe; Lin, Jing; Chen, Shouhui; Niu, Gang; Lu, Guangming; Chen, Xiaoyuan
<x xml:space="preserve">Abstract</x> Chlorin e6‐conjugated gold nanostars (GNSPEG‐Ce6) are constructed by X. Chen, G. Lu, and co‐workers on page 3055 as a novel theranostic system for imaging, and photodynamic and photothermal therapy. Utilizing the difference in photostability between chlorin e6 and gold nanostars, GNS‐PEG‐Ce6 can coordinate the early‐phase photodynamic effect with the late‐phase photothermal effect upon single wavelength continuous wave laser irradiation. With significantly improved anti‐cancer efficacy and simplified treatment process, the GNS‐PEGCe6 formula shows high potential for translation into clinical practice to treat cancer patients. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>